ON THE ROLE OF HISTOMORPHOMETRIC (STEREOLOGICAL) MICROSTRUCTURE PARAMETERS IN THE PREDICTION OF VERTEBRAE COMPRESSION STRENGTH - Wojnar, Leszek Karol; Gądek-Moszczak, Aneta; Pietraszek, Jacek (Image Analysis and Stereology, 2019)
The well-documented relation between bone mineral density (BMD) and bone compression strength constitutes the basis for osteoporosis diagnostics and the assessment of fracture risk. Simultaneously, this relation demonstrates a considerable scatter of results as bones of identical mineral density may have significantly different properties. The experimentally confirmed theorem that two materials or tissues of identical microstructure have identical properties leads to the evaluation of various quantitative stereological parameters (also referred to in biomedicine as histomorphology). These parameters, obtained from analysis of 2D or 3D images, have been used in numerous attempts to explain changes in bone strength. Although numerous correlation dependencies, often with high correlation coefficients, were evaluated, we do not know which parameters are worth evaluating, and there is no physical interpretation of these relations. An extended statistical analysis was accomplished on the basis of analysis of 3D images from 23 lumbar (L3) vertebrae scanned with micro-CT and the results of subsequent compression tests. A new parameter called SDF (structure destruction factor) was proposed in order to characterise the quality of 3D trabecular structures, and its significance was demonstrated. The final correlation function, which uses only three stereological parameters, made it possible to predict compression strength with considerable precision. The estimated values correlated very well with the apparent values (correlation coefficient r=0.96). Finally, the stereological parameters most suitable for characterisation of bone compression strength were chosen and a mechanism responsible for the changes in mechanical properties was proposed. The results obtained defined the necessary improvements in diagnostic techniques that would allow for more efficient quantitative microstructure evaluation and guidelines on how to improve treatment of patients with weakened bones.